Professionalism in Nursing: An Integrative Review of the Literature - Sakineh Parastesh; Mohammadali Hosseini; Farahnaz Mohammadi-Shahbolaghi; Sadat Seyyed Bagher Maddah; Abbas Ebadi (Journal of Holistic Nursing and Midwifery)
Introduction: Professionalism in nursing is a fundamental concept for providing effective and high-quality nursing care. Due to the complexity and multiple sides of this concept, it lacks a clear and precise definition. This ambiguity has created different and even poor interpretations of meanings and characteristics, making its accurate measurement difficult. Objective: This study aims to review the literature to provide the definition and attributes of “professionalism in nursing” and formulate a conceptual model for it. Materials and Methods: In the present study, the integrated review method was used in five stages: Specifying the problem, searching the literature, evaluating and extracting data, analyzing data, and presenting the results. The studies published in English or Persian were searched in international databases, such as CINAHL, EBSCO, PubMed, ProQuest, The Cochrane Library, EMBASE, SAGE, Science Direct, and Google Scholar search engine, as well as national databases, including SID, MagIran, IranDoc, and the medical sciences theses search engine. Results: After reviewing and analyzing 54 studies (17 qualitative studies, 27 quantitative studies, 4 mixed-method studies, 4 review studies, and 2 guidelines), the definition, attributes, antecedents, and consequences of “professionalism in nursing” were stipulated. The attributes included academic specialized knowledge, continuous pursuit of competence, autonomy, professional commitment, professional interaction, accountability, adherence to ethical principles and values, and advocacy. The antecedents were personal/occupational, organizational, and social factors. The consequences were individual and social outcomes. Conclusion: The results of integrative review of the literatures showed professionalism in nursing has evolved and encompassed new attributes and dimensions. Due to the comprehensiveness of the provided conceptual model, it can be used to design a tool to evaluate the professional qualities of nurses in their jobs.